2008
DOI: 10.1002/ccd.21317
|View full text |Cite
|
Sign up to set email alerts
|

Final kissing balloon inflation by classic crush stenting did not improve the clinical outcomes for the treatment of unprotected left main bifurcation lesions: The importance of double‐kissing crush technique

Abstract: Classic crush stenting with final kissing balloon inflations did not improve the clinical outcomes for the treatment of left main bifurcation lesion when compared with DK crush stenting technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
(31 reference statements)
2
14
0
Order By: Relevance
“…The former method introduces the first kissing inflation by the MV balloon and side stent without rewiring the SB, resulting in no real difference from the original crush. DK crush, focusing on the performance and quality of each kissing inflation using a noncompliant balloon in the SB, was associated with a significant reduction of TVR in the MV and SB (19,20). On the other hand, the routine use of FKBI after the 1-stent technique for simple bifurcations would not carry any advantage over that without FKBI (21), but without functional assessment (22).…”
Section: Discussionmentioning
confidence: 96%
“…The former method introduces the first kissing inflation by the MV balloon and side stent without rewiring the SB, resulting in no real difference from the original crush. DK crush, focusing on the performance and quality of each kissing inflation using a noncompliant balloon in the SB, was associated with a significant reduction of TVR in the MV and SB (19,20). On the other hand, the routine use of FKBI after the 1-stent technique for simple bifurcations would not carry any advantage over that without FKBI (21), but without functional assessment (22).…”
Section: Discussionmentioning
confidence: 96%
“…In the Nordic study [29], the classical crush stenting technique was associated with worse clinical outcomes, when compared with patients treated by the culotte technique. Our team also reported that the clinical outcomes after double-kissing crush stenting in patients with distal bifurcated unprotected LMCA [30] or entire bifurcation lesions [31] improved significantly, when comparing the outcomes with classical crush. The fact that the classical crush technique was used in 63% of patients treated by double-stent techniques raised concerns about the effect of classical crush on clinical outcomes in this study.…”
Section: Discussionmentioning
confidence: 97%
“…Although the presence of left main (LM) stenosis influences the complexity of PCI (3)(4)(5)(6)(7), clinical comorbidities likely also contribute to post-CABG clinical outcomes (8 -13). Although pre-treatment assessments with the European system for cardiac operative risk evaluation (EuroSCORE) and Parsonnet score (12,13) are widely advocated, their complex calculation and exclusion of procedural or lesion characteristics potentially limit their applicability in everyday practice.…”
mentioning
confidence: 99%